Effect of tallow (TAL) and crude soybean oil (CSBO) with or with out L-carnitine supplementation on carcass and serum lipid profile of male broiler chicken - SWARNA, CH LEELA; SRINIVAS, GURRAM; BORA, SWATHI (The Indian Journal of Animal Sciences, 2018)
The present experiment was conducted to study the effect of tallow and crude soybean oil with or without Lcarnitine supplementation on the carcass and lipid profile of male broiler chicks. Day old male broiler chicks (160) were divided into 4 treatments groups (T1, T2, T3 and T4) with eight replicates having five birds each. The T1 and T2 groups were fed with basal diets along with TAL and CSBO respectively without supplementation of carnitine, whereas T3 and T4 groups were fed with basal diets along with TAL and CSBO respectively with supplementation of carnitine @ 100 mg/kg diet. The fat sources with or without carnitine did not have significant effect on various carcass yields of broilers except for abdominal fat percentage, whereas interactions between fat sources and carnitine were significant. Abdominal fat content was significantly lower for crude soybean oil without carnitine. Carnitine supplementation had significantly increased moisture percentage of liver in case of fat source. Carnitine supplementation also significantly increased the fat content of liver, light and dark muscles. Serum triglycerides concentration was significantly lower for bird fed CSBO with 12 h fasting whereas, the concentration of triglycerides and cholesterol with 3 h fasting was significantly lower for birds fed with tallow diet. Serum triglyceride and cholesterol were significantly lower in carnitine supplementation groups.